1999
DOI: 10.33584/jnzg.1999.61.2349
|View full text |Cite
|
Sign up to set email alerts
|

Hill country farm investment options - cocksfoot pasture vs. superphosphate fertiliser

Abstract: Farmers can choose between investment in pasture species or fertiliser, however, there are few comparisons of these options. This paper reports on the effects of 'Grasslands Wana' cocksfoot, (Dactylis glomerata L.) introduction and superphosphate application on pasture production in hill country. The effects of pasture production on bullbeef production were subsequently modelled using Stockpol®. Pasture, bull and financial performance was measured within four self-contained farmlets (each approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The aim has been to manipulate the botanical composition of pasture swards towards the dominance of a few species with desirable animal forage characteristics (in terms of dry matter production, seasonal growth patterns and tissue digestibility). Consequently, much of New Zealand's pasture cultivar development and use has not only been dominated by a few species, mainly perennial ryegrass, Lolium perenne and white clover, Trifolium repens (Charlton and Stewart, 1999), but also to a lesser extent species such as cocksfoot, Dactylis glomerata (Barker et al. , 1985, 1999) and subterranean clover, T. subterraneum (Dodd et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim has been to manipulate the botanical composition of pasture swards towards the dominance of a few species with desirable animal forage characteristics (in terms of dry matter production, seasonal growth patterns and tissue digestibility). Consequently, much of New Zealand's pasture cultivar development and use has not only been dominated by a few species, mainly perennial ryegrass, Lolium perenne and white clover, Trifolium repens (Charlton and Stewart, 1999), but also to a lesser extent species such as cocksfoot, Dactylis glomerata (Barker et al. , 1985, 1999) and subterranean clover, T. subterraneum (Dodd et al.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has met with mixed success in hill country. Persistent gains in productivity and shifts in species composition have been demonstrated following the introduction of new species (Barker et al. , 1993, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Stevens et al (2000) showed that farm profitability increased substantially in Southland where new pasture performance peaked at 2 to 4 years; and the advantages over the original sward lasted for 10 to 14 years. Studies by Webby et al 1990 andBarker et al 1999 showed that new pasture species could be established to advantage in hill country. However, changes in seasonality of feed supply and feed quality do not necessarily have to occur through pasture improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of sociological research acknowledges that people play an extremely important part in the Field et al 1981;McCall et al 1986;Marshall et al 1991;Webby et al 1995;Rollo et al 1996;Woodward et al 2000;Ridler et al 2001;Woodward et al 2001;Rendel et al 2013;Spooner & Li 2013 Economic Beck & Dent 1987;Marshall et al 1991;Webby et al 1995;Ridler et al 2001;Rendel et al 2013 Environmental Synge et al 2013;Vogeler et al 2014White et al 2010Dynes et al 2011;Mackay et al 2012McCall 1984aMcCall 1984b;McCall et al 1986;Journeaux et al 1987;Parker et al 1992;Barker & Baars 1993;Stevens et al 2000;Webby & Sheath 2000;Murray et al 2007;White et al 2010;Dynes et al 2011;Mackay et al 2012;Beck & Dent 1987Journeaux et al 1987;Parker et al 1992;Korte & Rhodes 1993;Dake 1994;Barker et al 1999;Ormond et al 2002;Stevens et al 2000;Webby & Sheath 2000;White et al 2010;Dynes et al 2011;…”
Section: Sociology Researchmentioning
confidence: 99%